Terrestrial records of deglaciation events during terminations V and IV in the central Apennines (Italy) and insights on deglacial mechanisms - F. Marra; A. Pereira; B. Jicha; S. Nomade; I. Biddittu; F. Florindo; G. Muttoni; E. M. Niespolo; P. R. Renne; V. Scao (Scientific Reports, 2022)
Abstract 40Ar/39Ar geochronology constraints to aggradational phases and grain size variations show that the two large gravel beds occurring in the sedimentary filling of the Liri fluvial-lacustrine basin (central Italy) recorded the occurrence of deglaciation events synchronous within uncertainties with global meltwater pulses at ca. 450 and 350 ka. In particular, we find a precise match between the ages of gravel deposition and the occurrence of moderate sea-level rise events which anticipate those more marked during the glacial termination V and IV in the Red Sea relative sea level curve, as already verified by data from the Tiber River catchment basin. Such correspondence suggests that gravel deposition is facilitated by melting of Apennine mountain range glaciers, which provide the water transport energy and a surplus of clastic input to the rivers draining the mountain regions and flowing into the Tyrrhenian Sea. Therefore, the thick gravel beds intercalated in the sedimentary filling of the catchment basins of the major rivers in central Italy may be regarded as an equivalent proxy of large deglaciation events, similar to the ice-rafted debris in northern Atlantic. Consistent with this hypothesis, we also show the close correspondence between the occurrence of particularly mild (warmer) minima of the mean summer insolation at 65° N and these early aggradational phases, as well as with other anomalous early sea-level rises occurring c. 750 ka and 540 ka at the onset of glacial termination VIII and VI, and 40 ka at the onset of the so-called Heinrich events.